Endorsing and Reinforcing Gender and Age Stereotypes: The Negative Effect on Self-Rated Leadership Potential for Women and Older Workers - Tresh, Fatima; Steeden, Ben; Randsley de Moura, Georgina; Leite, Ana C.; Swift, Hannah J.; Player, Abigail (Frontiers in Psychology, 2019)
Previous research has examined the impact of stereotypes on outcomes such as career progression and hiring decisions. We present a novel approach to examine the role of stereotypes in predicting self-rated leadership potential across gender and age groups. This research sheds light on the impact of leadership-incongruent and detrimental stereotypes about one’s gender and age, for women and older workers, on self-ratings of leadership potential. Across three studies (total N = 640), correlational and experimental evidence shows differential effects of stereotypes about women (vs. men) and older (vs. younger) people on self-ratings of their own leadership potential. Specifically, results suggest that both gender and age stereotypes affect older workers more than their younger counterparts (Study 1). We examined the effects of stereotyped workplace cultures and found comparable effects on self-rated leadership potential at the intersectional level, with women self-rating more leadership potential than men in the younger but not the older age group (Study 2). Furthermore, stereotyped workplace cultures impacted women’s and older worker’s perceptions of job fit (Studies 2 & 3), also extending to job appeal for older workers (Study 3). Results are discussed in terms of career implications for both women and older workers, with a particular focus on older women, whose intersecting identities are leadership stereotype-incongruent.